Development of the approach to proving the security of Grostl-like hashing algorithms to rebound attacks - Ruzhentsev, Victor; Onishchenko, Yurii; Svitlychnyi, Vitalii (Eastern-European Journal of Enterprise Technologies, 2017)
An approach for estimating the security of Grostl-like hashing algorithms to collision rebound attacks is proposed. The Kupyna algorithm, adopted as the new Ukrainian standard of hashing, belongs to this kind of hash functions. The proposed approach is based on determining the boundary number of rounds for each stage of the transformation of the difference (fragment of the byte differential characteristic). The boundary number of rounds for the inbound part of the byte differential characteristic is determined based on an analysis of the results from known works. The boundary number of rounds for outbound parts of the byte differential characteristic is determined based on the known probability constraints for Rijndael-like ciphers. The proposed approach is applied to the Kupyna algorithm, adopted as the national Ukrainian standard DSTU 7564: 2014. It is shown that the presence of 5 or more rounds in each of the P and Q transformations of this hashing algorithm makes it resistant to rebound attacks